27-Hydroxycholesterol, The Estrogen Receptor Modulator, Alters DNA Methylation in Breast Cancer - Vini, Ravindran; Rajavelu, Arumugam; Sreeharshan, Sreeja (Frontiers in Endocrinology, 2022)
27-hydroxycholesterol (27-HC) is the first known endogenous Selective Estrogen Receptor Modulator (SERM) and its elevation from normal levels is closely associated with breast cancer development. A plethora of evidences suggests that aberrant epigenetic signatures in the breast cancer cells can result in the differential responses to various chemotherapeutics and leading to the development of resistant cancer cells. Such aberrant epigenetic changes are often dictated by the microenvironment. The local concentration of oxygen and metabolites in the microenvironment of breast cancer are known to influence the development of breast cancer. Hence, we hypothesised that 27-HC, an oxysterol, which been shown to induce breast cancer progression via ERα, LXR and by modulating immune cells, may also induce the epigenetic changes. For deciphering the same, we treated the estrogen receptor positive cells with 27-HC and identified DNA hypermethylation on a subset of genes by performing DNA bisulfite sequencing. The genes which showed significant DNA hypermethylation were phosphatidylserine synthase (PTDSS2), MIR613, indoleamine 2,3-Dioxygenase 1(IDO1), thyroid hormone receptor alpha (THRA), Dystrotelin (DTYN), Mesoderm induction early response 1, family member 3 (MIER). Further, we have identified that the 27-HC has weakened the DNMT3B association with the ERα in MCF7 cells. This study reports that 27-HC induces aberrant DNA methylation changes on the promoters of a subset of genes through modulation of ERα and DNMT3B complexes to induce the local DNA methylation changes, which may dictate the drug responses and breast cancer development.